Food security, poverty and nutrition policy analysis : statistical methods and policy applications. - Babu, Suresh Chandra; Gajanan, Shailendra N.
Food Security, Poverty and Nutrition Policy Analysis: Statistical Methods and Applications, Third Edition combines statistical data analysis and computer literacy, applying the results to develop policy alternatives through a series of statistical methods for real world food insecurity, malnutrition and poverty problems. The book presents the latest uses of statistical methods for policy analysis using the open source statistical environment R, in addition to having the original Stata files and applications. A new chapter on obesity brings in new datasets for analysis to effectively demonstrate the use of such data for addressing policy issues. Finally, program evaluation methods which can be directly applied to the data on food security, nutrition, poverty indicators and causal factors are included. This unique, real-world data takes the reader through a "hands-on" approach toward econometric practice whereby they can also test the effects of policy and program interventions. Further, this is the first book to explore actual data with STATA and R statistical packages that also provides a line-by-line guide to the programming and interpretation of results. --
Section I: Food Security Policy Analysis. 1. Introduction to food security: concepts and measurement 2. Implications of technological change, post-harvest technology and technology adoption for improved food security -- application of t-statistic 3. Effects of commercialization of agriculture (shift from traditional crop to cash crop) on food consumption and nutrition -- application of chi-square statistic 4. Effects of technology adoption and gender of household head: The issue, its importance in food security -- application of Cramer's V and phi coefficient 5. Changes in food consumption patterns: Its importance to food security -- application of one-way ANOVA 6. Impact of market access on food security -- application of factor analysis Section II: Nutrition Policy Analysis 7. Impact of maternal education and care on preschoolers' nutrition -- application of two-way ANOVA 8. Indicators and causal factors of nutrition -- application of correlation analysis 9. Effects of individual, household and community indicators on child's nutritional status -- application of simple linear regression 10. Maternal education and community characteristics as indicators of nutritional status of children -- application of multivariate regression Section III: Special Topics on Poverty, Nutrition and Food Policy Analysis 11. Predicting child nutritional status using related socioeconomic variables -- application of discriminant function analysis 12. Measurement and determinants of poverty -- application of logistic regression models 13. Classifying households on food security and poverty dimensions -- application of K-mean cluster analysis 14. Household care as a determinant of nutritional status -- application of instrumental variable estimation 15: Achieving an ideal diet -- modeling with linear programming 16. Food and Nutrition Program Evaluation.
Previous edition: 2014.
Includes bibliographical references and index.
Keywords: Food supply; Nutrition policy; Politique alimentaire; Food supply